E-MODULES BASED ON MULTI-REPRESENTATIONS ON NEWTON'S LAW MATERIALS - Chieka Mariskha; Ika Mustika Sari; Irianto Tedja; Hera Novia (UIN Sunan Gunung Djati Bandung, 2022)
With the use of ICT, the use of e-modules as a learning resource has become an innovation. E-modules are independent study materials in electronic format by utilizing various media and interactive features as well as learners' learning experiences. This e-module characteristic supports the presentation of physics teaching materials in the form of multiple representations. However, the availability and use of multiple representation-based e-modules is still limited, given the importance of learning resources and multiple representations so this research conducts a multi-representation based e-module preparation on Newton's Law material. The research method used is R&D with an adaptation development model of the 4D development model which is carried out through the Define, Design, and Develop stages. The e-module product that has been compiled is validated by four experts and 15 students as initial users. The results of the validation analysis show that the qualified e-modules are qualified properly in the aspects of content, media and multiple representation. In the developmental testing, a positive response was obtained and the results showed that the readability of the e-module was